MDFIC2 is a PIEZO channel modulator that can alleviate mechanical allodynia associated with neuropathic pain - Abdella M. Habib; Shengnan Li; Chenjing Zhang; Meijun Ji; Nancy Osorio; Virginie Penalba; Jesus M. Torres; Samuel J. Gossage; Mehdi A. Rezai; Amy F. Geard; Ahad A. Rahim; Ahmed M. M. Mahmoud; et al. (Proceedings of the National Academy of Sciences, 2025)
PIEZO channels are mechanical force sensors involved in various biological processes, including somatosensation. To date, only a few PIEZO-binding partners have been identified, including MyoD-family inhibitor proteins (MDFI and MDFIC). Here, we show that MDFIC2, a third member of the MDFI protein family with an as-yet-unknown function, is expressed in a subset of nociceptive sensory neurons. MDFIC2 modulates both PIEZO1 and PIEZO2 gating properties by slowing their kinetics and shifting mechanical sensitivity to higher forces. Interestingly, Mdfic2 is downregulated in mouse neuropathic pain models in which mechanical allodynia is a hallmark symptom. We found that intrathecal administration of adeno-associated virus vector encoding MDFIC2 cDNA reduces mechanical sensitivity and attenuates mechanical allodynia in the spared nerve injury neuropathic pain model. These findings demonstrate a mechanism for regulating mechanosensation and highlight a potential therapeutic route for treating mechanical allodynia.